Sulfonated Polysulfone/PEG/Halloysite Nanotube Hybrid Tight-Ultrafiltration Membranes for Treatment of Industrially Contaminated Raw Water - Okinawa, Jessica Enis; Agustin, Diva Amerya; Annisa, Rani; Putri, Tiara Ariani; Aryanti, Putu Teta Prihartini (Reaktor, 2025)
The quality of river water in Indonesia predominantly falls below the established standards for clean water, including the Citarum River in West Java. Despite the associated health risks, many residents in the river basin continue to utilize this water for their daily needs. This study aims to develop tightly structured ultrafiltration membranes (tight-UF) capable of treating contaminated raw water into clean water. The tight-UF membranes were fabricated using sulfonated polysulfone (SPSf, 20% by weight), blended with polyethylene glycol (PEG400, 20% by weight), and halloysite nanotube additives (HNT, 1-2% by weight) in a solvent mixture of acetone and dimethylacetamide (Ac/DMAc). SPSf was synthesized using a sulfonation technique involving immersion in sulfuric acid at concentrations of 70% and 98%. The findings indicate that increasing the acetone concentration decreases the porosity and increases the membrane skin thickness. Additionally, the inclusion of HNT up to 2% resulted in reduced membrane selectivity due to particle agglomeration. The optimal formulation was identified at concentrations of SPSF/PEG400/HNT/Ac of 20/20/1/5% by weight, yielding a rejection rate of 98.57% and a flux of 63.45 L/m².h at 98% SPSF. These results underscore the potential of tight-UF membranes for applications in clean water treatment from contaminated water sources.